Efeitos neuroimunológicos do tratamento por nebulização de nanopartículas lipídicas sólidas contendo dimetil fumarato e lipossomas contendo angiotensina-1-7 em animais com encefalomielite autoimune experimental - Bárbara Fernandes Pinto (2022)
Multiple sclerosis (MS) is a chronic, progressive, autoimmune disease characterized by inflammatory infiltrates, gliosis, demyelination, and axonal degeneration in the central nervous system (CNS). Several forms of treatment have been used to minimize the clinical symptoms of MS. However, many of these drugs are expensive, have serious adverse effects and inconvenient forms of administration, reducing patient compliance. Therefore, it is important to search for new routes of administration and therapeutic strategies for the treatment of MS. The aim of this study was to evaluate the neuroimmunological effects of nebulization treatment of solid lipid nanoparticles (SLN) containing dimethyl fumarate (DMF), and of liposomes containing Angiotensin-1-7 (Ang-1-7), in mice with experimental autoimmune encephalomyelitis (EAE). The EAE model was induced in 8- to 12-week-old female C57Bl/6 mice by subcutaneous administration of emulsion containing MOG 35-55 peptide, Mycobacterium tuberculosis and Freund's complete adjuvant (CFA), followed by i.p. injection of pertussis toxin. The experimental groups received the respective treatments by nebulization for 20/21 days, every 72 hours, totalizing 7 administrations. The treatments consisted of nebulization of: a) 0.9% saline solution, b) empty SLN, c) SLN with DMF, d) empty liposomes, e) Ang-1-7, or f) liposomes with Ang-1-7. Every 72 hours, body weight and clinical score were analyzed, and at the end of treatment, data regarding CNS inflammation, pulmonary and systemic toxicity were collected. The inhaled administration of both DMF in SLN and Ang-1-7 in liposomes were effective in treating EAE animals, improving the clinical score and inflammatory response. No pulmonary toxicity associated with the use of SLNs and liposomes was evidenced. For the first time, our results show that (untreated) EAE animals showed inflammation and worsening of lung function, and that DMF in SLN and Ang-1-7 in liposomes attenuated these effects. In summary, it is suggested that nebulization of nanostructures containing DMF or Angiotensin 1-7 may be a potential therapeutic protocol for the treatment of MS, since it contributes to increase the effectiveness of the drug.